CLOUD SERVICE SELECTION FRAMEWORK FOR SUPPLY CHAIN OPTIMIZATION: A MULTI-CRITERIA DECISION ANALYSIS APPROACH - Satish Anchuri, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
In today's fast-paced, globalized economy, supply chain optimization has become essential for maintaining competitiveness. Cloud computing plays a crucial role in transforming supply chain management by offering scalable, flexible, and cost-effective solutions. However, selecting an appropriate cloud service provider requires careful evaluation due to diverse factors, including security, integration capabilities, cost, and performance reliability. This article presents a Cloud Service Selection Framework for Supply Chain Optimization, utilizing a Multi-Criteria Decision Analysis (MCDA) approach. By evaluating key criteria, this framework enables organizations to make well-informed decisions aligned with their operational and strategic goals. Case studies from the retail and logistics sectors demonstrate the practical applications and benefits of this approach.